Biotechnology : Applying the Genetic Revolution - Clark, David P Pazdernik, Nanette Jean (Academic Press/Elsevier, 2009)
"Unlike most textbooks on this subject, Biotechnology approaches modern biotechnology from a molecular basis. Using straightforward, less technical jargon, Clark and Pazdernik introduce students to the topics and walk them through the process as it evolves into a more specific detailed principle." "This up-to-date text covers a wide realm of topics that are encountered in current media and movies. One of the chapters covers the burgeoning field of nanobiotechnology, stimulating the student to think about biotechnology from a new and much smaller point of view. Another chapter explains the real biotechnology behind crime scene investigations portrayed so dramatically on the hit show CSI. In addition, students will learn about the biotechnology behind making vaccines, genetically-modified plants, stem-cell research, gene therapy, and aging, among many other topics that are part of mainstream media coverage. Students will also learn the molecular basis for many viral diseases, cancer, and bacterial diseases that are bound to affect them or other family members. Finally, the text includes a very thought-provoking chapter on the bioethics of these new advances and applications of today's world of biotechnology, which stimulates the student to think rather than memorize."--BOOK JACKET.